MODEL BESAR KLAIM (SEVERITY) YANG DIAJUKAN RUMAH SAKIT KEPADA BPJS KESEHATAN - Eva Binsasi (KH. A. Wahab Hasbullah University, 2016)
Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan is a public legal entity established by the Indonesian government to execute the Jaminan Kesehatan Nasional (JKN) program. In implementing the program, BPJS Kesehatan cooperates with the first level and the referred advanced level health facilities. The payment system that BPJS Kesehatan used to pay claims reported by the referred advanced level health facility (the hospital) is the Indonesia-Case Based Groups (INA-CBGs). It is assumed that there is a difference between the inpatient claims severity reported by the hospital and the claims severity paid by BPJS Kesehatan. This research aims to model the inpatient claims severity reported by a hospital using a Generalized Linear Model (GLM). In this research, the data used as a case study is inpatient claims severity data of BPJS Kesehatan participants at a type-D hospital in East Nusa Tenggara from January to December 2014. According to Kolmogorov-Smirnov and Anderson Darling tests, at 1% level of significance, it is found that each of the inpatients claims severity variables at three hospital room classes follow an Inverse Gaussian distribution. Variables which are significantly determining the inpatients claims severity reported by the hospital are: “Length of Stay (LOS)”, “INA-CBGs”, “severity level”, and “age” for Class-1 patients; “LOS”, and “INA-CBGs” for Class-2 patients; and “LOS”, “gender”, “cara pulang”, “age” and “severity level” for Class-3 patients; where the dominant variable is “LOS”. Keywords: Generalized Linear Model (GLM), BPJS Kesehatan, claims severity